Theorem on the central manifold of a nonlinear parabolic equation - Belan, E. P.; Lykova, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
Under certain assumptions, we prove the existence of an m-parameter family of solutions that form the central invariant manifold of a nonlinear parabolic equation. For this purpose, we use an abstract scheme that corresponds to energy methods for strongly parabolic equations of arbitrary order.